Preparation of AC/TiO2 doped N-Ce Synthesized via Microwave Irradiation for Amoxicillin Photodegradation - Abdul Rahman, Nur Athirah Awatif; Khasri, Azduwin; Ahmad, Anis Atikah; Mohd Jamir, Mohd Ridzuan; Mat Yasin, Nur Hidayah (International Journal of Integrated Engineering, 2024)
Activated carbon (AC) supported with titanium dioxide (TiO2) doped with Nitrogen (N) and Cerium (Ce) were synthesized for adsorption and photodegradation of amoxicillin antibiotic. Optimization of the modified AC/TiO2 composite was developed for removal amoxicillin from aqueous solution using sol-gel method assisted with microwave radiation under UV Light. In this work, four variables were optimized via Central Composite Design (CCD) under Response Surface Methodology (RSM) and they were urea (N source) (A: 0.02 g – 0.2 g), cerium (III) nitrate hexahydrate (Ce source) (B: 0.02 g – 0.2 g), activated carbon dosage (C: 0.1 g – 0.5 g) and microwave power (D: 600 W – 800 W) to observe amoxicillin degradation. Under optimum variables preparation, results indicated that the modified AC/TiO2 photocatalyst prepared with 0.5 g activated carbon, doped with 0.02 g urea and 0.2 g cerium exhibited 93.6 % amoxicillin removal under UV light.